Mechanisms of Cu2+ biosorption on Lessonia nigrescens dead biomass: Functional groups interactions and morphological characterization. Issue 2 (April 2018) - Cid, Héctor A.; Flores, Marcos I.; Pizarro, Jaime F.; Castillo, Ximena A.; Barros, Daniel E.; Moreno-Piraján, Juan C.; Ortiz, Claudia A.
Graphical abstract: Abstract: In this study, the biosorption mechanisms of Cu 2+ by dead biomass of the brown seaweed Lessonia nigrescens were characterized, with special emphasis on the chemical environment provided by functional groups, their interactions with the metal, and the induced morphological changes triggered by the biosorption process. The morphological changes on the seaweed surface were characterized by SEM and AFM techniques, before and after the exposure of the biomass to Cu 2+ ions. ATR-FTIR, EDS and XPS were used to characterize the chemical atomic environment on the seaweed biomass, to determine the biosorption saturation times of the founded functional groups, and the changes on the biomass surface composition, and main chemical bondings. The use of these techniques revealed that this seaweed biomass interacts with Cu 2+ ions mainly through carboxyl, sulfonate and hydroxyl groups, by ionic and coordinative bonds by ligand multidentism, and rearrangements of the cell wall stiffness.